Assessment of in-vivo safety and antibacterial activity of phages against methicillin resistant S. aureus in mouse model (Indian Journal of Traditional Knowledge (IJTK), 2024)
Traditionally Ganges water that contains bacteriophages, are used in Hindu rituals in India. Bacteriophages are bacterial-specific viruses and present abundantly on Earth. They are present most widely in the biosphere, soil and the intestine of animals. Specificity of infection makes them a powerful alternative for the control of bacterial infection which is normally showing resistant to antibiotics. In present study, isolation of bacteriophage was carried out from sewage of piggery and dairy farms to find out antimicrobial property. Isolated bacteriophages were showing an icosahedral symmetry with long tail of 109 nm and head of 52.20 nm in diameter under electron microscopic observation. These phages were considered as member of Myoviridae family. Presently, antimicrobial resistance is an acute problem across the globe, and therefore alternate for antimicrobials should be searched on priority. Primary aim of this study was to isolate and evaluate the efﬁcacy of a bacteriophage against Multi drug resistance pathogen like Methicillin resistance Staphylococcus aureus. A total 150 sewage samples were processed for bacteriophage isolation out of them 27 were found to be positive for bacteriophages. Four isolates of bacteriophage lysate ØVS1, ØVS5, ØVS9 and ØVS 27 were used as a Cocktail in trail. Therapeutic and safety profile of the purified phage lysate cocktail were performed in well-defined mouse model at laboratory animal house of College of Veterinary Science & A.H., Jabalpur (M.P.). Results showed 100% in mice G-III (challenged with MRSA) was treated with phage Cocktail with in ten days whereas G-IV was showing approx. 40% in abscess (challenged with MRSA). Our findings reported that the bacteriophage therapy is safe and better than traditional antibiotics therapy especially in multidrug resistance cases.